Hindlimb lameness and gait abnormalities in bitches with pyometra. (12th July 2014) - Klainbart, S.; Ranen, E.; Glikman, G.; Kelmer, E.; Bdolah‐Abram, T.; Aroch, I.
Abstract : The objective of this study was to assess the frequency of gait abnormalities and lameness (GAL) in bitches with pyometra, and their association with clinical and laboratory findings. The study included 79 bitches diagnosed with pyometra and 35 negative control intact bitches presented with other soft tissue surgical disorders. Dogs with a history of chronic lameness due to orthopaedic or neurological origin were excluded. A history of GAL was more frequent in the pyometra group (47 per cent) compared with the control group (20 per cent) (P=0.007). In the pyometra group, bitches presenting GAL had (P<0.04) higher frequencies of closed‐cervix pyometra, anorexia and vomiting, as well as higher serum creatinine concentration and muscle enzymes activity, compared with those in without GAL. GAL signs resolved postovariohysterectomy in all but one bitch. The results suggest that GAL signs occur frequently in bitches with pyometra, especially in closed‐cervix disease. Therefore, pyometra should be considered among the differential diagnoses when GAL occurs, especially when the clinical signs are non‐specific and the reproductive history is unclear.